Terapias para la comunicación en personas con esclerosis múltiple - Tapia S., Sara; Matus R., Paulina (Revista Hospital Clínico Universidad de Chile, 2022)
People with Multiple Sclerosis (MS) can present a variety of communication disorders that affect their roles and social participation, affecting their quality of life and that of their environment. An early approach to these people and their communication difficulties could improve/compensate/facilitate communication, minimizing the effects on their daily life. Purpose: To contribute with recommendations for communication therapy in people with MS. Method: narrative literature review related to the topic. Results: There are few investigations focused on the intervention of communication in people with MS, those found are works in small populations, with evaluations at the beginning and at the end of therapy. The most promising studies are those that show specific effects on speech, through the LSVT LOUD, which not only improves communicative effectiveness, but has also shown improvements in dysphagia (eating disorder). significant to consider interventions with the environment and aimed at the quality of life of the affected individuals and families. Conclusions: The different presentations that MS has and its individual characteristics in each person, makes it difficult to have specific evidence on the most effective types of therapy. Despite this, it is possible to use therapies focused on different communication symptoms and adapt them under certain considerations to address communication in people with MS.